Moderne mitološke transformacije v pesniškem ciklu Odisej Gregorja Strniše - Živković, Dušan (Slavistična revija, 2014)
In this article we analyze the bases, processes, and functions of mythic transformations in Gregor Strniša's poetic cycle "Odysseus." Comprehending the past allows us to recognize the Derridean play of differences and ambiguity; the subject of Strniša's poetry reveals humanity's wandering experience as an experience outside the traditional metaphysical distinction between life and death. Strniša's new poetic mythology allows images from ancient worlds to establish themselves afresh in a variety of perspectives-conveying this by means of complex optics of consciousness in order to express twentieth century experiences. His new mythical world presents a mysterious dimension where signs of the invisible are simultaneously hints that conceal not only the exotic meaning of the past, but also the dark ontological origin of the sum of past events and modern stories about them.
Keywords: mitologija; myth; mythology; ontologija; ontology; signs; Slovene literature; Slovene poetry; Slovene poets; slovenska književnost; slovenska poezija; slovenski pesniki; Strniša, Gregor, 1930-1987; znaki